The Effectiveness of SW (Student Worksheets) Based on STEM (Science, Technology, Engineering, Mathematics) to Train Students' Creative Thinking Skills - Anugrah Agustina; Yuni Sri Rahayu; Yuliani Yuliani (Universitas Muhammadiyah Sidoarjo, 2021)
Existing learning has not fully facilitated 4C (critical thinking, communication, collaboration, and creativity) skills and there are obstacles for students to encounter in studying biology, especially the material about plant tissue. It happens due to various limitations in achieving basic competency skills. One of the learning approaches that can be used to support 4C skills is the STEM approach which is supported by student worksheets (SW) to guide the learning process. The purpose of this study was to measure the effectiveness of STEM-based SW to train students' creative thinking skills. The research method used is descriptive quantitative and qualitative with one group pre-test and post-test design. The research subjects were 21 students of XI grades at SMAK St.Hendrikus. Data analysis of the N-Gain test of creative thinking skills obtained an average N-gain of 0.7 with a medium category. The N-Gain analysis of creative thinking skills using the T-Test with a sig. (2-tailed) value of 0.000 indicates that STEM-based worksheets are effective in training students' creative thinking skills.